Higher education provision using systems thinking approach – case studies. (2nd January 2018) - Dhukaram, Anandhi Vivekanandan; Sgouropoulou, Cleo; Feldman, Gerald; Amini, Ardavan
ABSTRACT: The purpose of this paper is to highlight the complexities involved in higher education provision and how systems thinking and socio-technical systems (STS) thinking approach can be used to understand the education ecosystem. Systems thinking perspective is provided using two case studies: the development of European Learner Mobility (EuroLM) service and the delivery of Enterprise System Management (ESM) course at the Birmingham City University, UK. The case studies present how systems thinking using STS approaches like applied organisational change and Cognitive Work Analysis can be used to capture a conceptual model of the education system for understanding the interactions and relationships between the people, technology, processes and the organisations. Using systems thinking perspective, EuroLM has developed a set of technical standards addressed to the European systems developers and ESM delivery ensures that students communicate and collaborate.